Preliminary of Cognitive and Systemic Disorders in Rats Due to Chronic Exposure to Aluminum Chloride - Haniyeh Amini; Manizheh Karami (Caspian Journal of Neurological Sciences, 2025)
Background: Aluminum is a heavy metal (HM) that negatively affects the brain and other body organs. The hippocampus, which is primarily involved in learning and memory, is susceptible to toxins. Internal organs may also be damaged in Alzheimer disease (AD), especially with chronic exposure to HM. Objectives: We induced cognitive impairment (CI) in rats by chronic consumption of AlCl3 (Al) in the drinking water and examined their hippocampus, liver, and serum lipid profiles. Materials & Methods: Animals (Wistar rats weighing about 250 g) were randomly divided into two control groups that received water and four experimental groups that were treated with volumetric concentrations of Al in drinking water (10 mg/kg and 50 mg/kg). The duration of treatment was two weeks for some rats and four weeks for others. At the end of each period, the animals experienced novelty-seeking (NS) for three days and then were deeply anesthetized, and their heart’s blood was taken. The brain and liver were then examined surgically. The data were evaluated using analysis of variance (ANOVA) at a significant level of α=0.05. Results: Based on the NS test, Al administration for 2-4 weeks had an adverse effect on memory retrieval, and a significant increase in serum glutamic oxaloacetic transaminase (SGOT) levels and changes in lipid profile were also shown as representative of early liver damage. Conclusion: Aluminum damages the brain and causes liver dysfunction due to its chronic consumption.